CALCULATION OF A GOODS COMPETITIVENESS AS AN APPROACH TO EVALUATION OF COMPETITIVENESS OFTRADING NETWORKS - A. A. Yarlychenko; A. M. Naida; E. M. Gotlib (Russian Journal of Economics and Law)
The article presents a summary of the known techniques of evaluating the competitiveness of trading networks and gives an example of its calculation basing on the goods quality.